2008
DOI: 10.1590/s1519-566x2008000500001
|View full text |Cite
|
Sign up to set email alerts
|

The chemical volatiles (Semiochemicals) produced by neotropical stink bugs (Hemiptera: Pentatomidae)

Abstract: Os Voláteis Químicos (Semioquímicos) Produzidos pelos Percevejos Neotropicais Hemiptera: Pentatomidae) RESUMO -Nos últimos anos tem sido crescente a preocupação com as mudanças climáticas e com a utilização auto-sustentável dos recursos naturais, estimulando cada vez mais os estudos para a prospecção de novos produtos naturais visando minimizar o uso de pesticidas. Os percevejos produzem uma variedade de compostos químicos com potencial para o seu manejo. A composição química dos compostos defensivos dos perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
0
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 105 publications
2
72
0
8
Order By: Relevance
“…The results of this study strongly suggest a defensive role for the blends emitted by the two species: (i) the chemicals were secreted only in response to disturbance 20 and (ii) many constituents are found in other heteropteran defensive secretions 2,21,22 and are known to have toxic, irritating or deterrent properties. 18,23 However, these results also suggest that some volatile constituents may have the role of sex pheromones, both because they were absent in nymphs (i.e., sexually immature individuals) and because of the differences detected between male and female adults, mainly in Phloeophana longirostris.…”
Section: Volatile Compounds From the Bark Bugs Phloea Subquadrata Andmentioning
confidence: 70%
“…The results of this study strongly suggest a defensive role for the blends emitted by the two species: (i) the chemicals were secreted only in response to disturbance 20 and (ii) many constituents are found in other heteropteran defensive secretions 2,21,22 and are known to have toxic, irritating or deterrent properties. 18,23 However, these results also suggest that some volatile constituents may have the role of sex pheromones, both because they were absent in nymphs (i.e., sexually immature individuals) and because of the differences detected between male and female adults, mainly in Phloeophana longirostris.…”
Section: Volatile Compounds From the Bark Bugs Phloea Subquadrata Andmentioning
confidence: 70%
“…The morphology of the immature stages and some biological aspects of these two Chinavia species have already been reported (Grazia et al, 1982, Schwertner et al, 2002, and a preliminary laboratory study showed that C. impicticornis and C. ubica have similar development time, high fecundity (Laumann et al, 2006), and an efficient intraspecific communication during the reproductive stage, by means of chemical and vibratory signals (Moraes et al, 2005(Moraes et al, , 2008.…”
Section: Introductionmentioning
confidence: 88%
“…Tibraca limbativentris is a pest of paddy rice in Argentina, Brazil, and Uruguay, and the coreid ("leaf-footed bug") Leptoglossus zonatus damages corn and other plantations in Brazil. The pheromone chemistry of Heteroptera has been reviewed comprehensively 46 and also with a focus on neotropical species, 47 and here we will only refer to examples which are within the scope of the present review.…”
Section: Heteropteramentioning
confidence: 99%